Do we know what they know? Comparing US and French undergraduate students' knowledge of core business concepts. Issue 8 (10th August 2015) - Naatus, Mary Kate; Passerini, Katia; Pon, Kevin; Somers, Mark
Abstract : Purpose: – The purpose of this paper is to compare knowledge of business concepts acquired at the end of undergraduate studies of management in France and the USA. Design/methodology/approach: – Mind maps were used to examine what knowledge students retained toward the end of their undergraduate studies in business and management. Data were collected from two groups of students, one in France and one in the USA and they analyzed on computer software. Findings: – The results indicate that the learning process may be influenced not only by the structure and content of the program but also by the environment in which such content is assimilated. This study provides examples of how culture can influence the way we learn and represent core business knowledge. Research limitations/implications: – The research was based on a number of undergraduate students and cannot therefore be generalized to other subjects or other levels of studies at the present time. Originality/value: – The paper moves away from traditional manners of collecting data through questionnaires and surveys in order to study the impact of management education and what students learn at undergraduate level.